Tanggap Pertumbuhan Bibit Tebu Merah (Saccharum officinarum L.) Asal Bud Set terhadap Pemangkasan dan Frekuensi Penyiraman - Hartanto, Supriadi; Irsal; Barus, Asil (Jurnal Online Pertanian Tropik, 2018)
This research was conducted to determine the growth of red sugarcane seedling on pruning and frequency of watering. This research was conducted in the research field of Faculty of Agriculture University of Sumatera Utara (± 25 m asl) from June-October 2017 using Factorial Randomized Block Design with three replications. The first factor was pruning (control, 1, and 2 months/plant) as well as the second factor was the frequency of watering (1, 3, 5, and 7 days/plants). The variable observed were plant height, a number of leaves, stem diameter, a number of the tiller, shoot wet weight, root wet weight, and shoot-root ratio. The results showed that the frequency of watering treatment had a significant effect on the number of a leaf (4,6,8,10 and 12 weeks after plant), stem diameter (4,6,8,10 and 12 weeks after plant), shoot wet weight, and root wet weight. Pruning treatment had no significant effect on all variables observed. The interaction of both has no significant effect on all variables observed.